لبصمة الوراثية، تحليل الحامض النووي، اثبات النسب. - سلخ, محمد لمين (University of Eloued جامعة الوادي, 2021)
يرى جانب من الفقه أن الهدف من تحرير شهادة طبية وتسليمها وفق الشروط الشكلية والموضوعية المتطلبة قانونا لذلك، دون الإخلال بالالتزامات القانونية الملقاة على عاتق الطبيب في هذا الجانب، وكذا مقتضيات الالتزام بالسر المهني في هذا المجال، يكون من أجل استعمالها كوسيلة إثبات أمام جهة قضائية أو إدارية ما، لكن بالمقابل يرى جانب آخر من الفقه أن الشهادة الطبية عندما تقدم أمام القضاء الجزائي تحديدا لا تعتبر وسيلة إثبات، وإنما هي سند مكتوب تبين الحالة الصحية للشخص المعني بها، حيث أن هذا الجدل الفقهي حول القيمة الإثباتية للشهادة الطبية يدفعنا إلى البحث في هذا الموضوع ومحاولة الإجابة عنه من خلال هذا المقال. Abstract: Regarding the medical certificate that meets all the formal and substantive conditions required by law, without any breach to the legal obligations imposed on the medical practitioner in this aspect, as well as maintaining the professional confidentiality, several jurists consider that the purpose of its issuance and delivery is for it to be used as a means of proof before a judicial or administrative authority. On the other hand, another group of jurists considers that the medical certificate is not considered as means of proof when presented before the criminal court, but rather a written document indicating the health status of the concerned person. This jurisprudential debate about the probative value of the medical certificate prompts us to research this topic and try to undertake it in this article.
Probative Value Of The Medical Certificate - A Comparative Study
مقال
Keywords: دور إباضية المغرب الأوسط في تنشيط التجارة الصحراوية خلال العصر الوسيط; Medical certificate; proof; judiciary; probative value; Medical Practitioner.